2010
DOI: 10.1021/cn900019r
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Peptides Derived from Terminal Modifications of the Aβ Central Hydrophobic Core on Aβ Fibrillization

Abstract: Considerable research effort has focused on the discovery of mitigators that block the toxicity of the β-amyloid peptide (Aβ) by targeting a specific step involved in Aβ fibrillogenesis and subsequent aggregation. Given that aggregation intermediates are hypothesized to be responsible for Aβ toxicity, such compounds could likely prevent or mitigate aggregation, or alternatively cause further association of toxic oligomers into larger nontoxic aggregates. Herein we investigate the effect of modifications of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 57 publications
1
32
0
Order By: Relevance
“…1115 Seeking to leverage this precedent toward biomedical application, recent studies have shown that strategic incorporation of bulky α,α-dialkylated amino acids (e.g., diisobutylglycine, dibenzylglycine, di- n -propylglycine) into short β-strands can cap growing β-sheets, preventing formation of amyloid fibrils and even promoting their disassembly. 1618 …”
mentioning
confidence: 99%
“…1115 Seeking to leverage this precedent toward biomedical application, recent studies have shown that strategic incorporation of bulky α,α-dialkylated amino acids (e.g., diisobutylglycine, dibenzylglycine, di- n -propylglycine) into short β-strands can cap growing β-sheets, preventing formation of amyloid fibrils and even promoting their disassembly. 1618 …”
mentioning
confidence: 99%
“…Spherical particles were previously reported for mixtures of Ab 1-40 with a Lys-Leu-Val-PhePhe-peptide-based inhibitor that has neutral mini-polyethylene glycol (PEG) groups at its C-and N-termini. [15] The incubation of Ab [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] with conjugates 3 and 4 resulted in the formation of mostly spherical particles (Figures 2 f and g). In the case of Ab 12-28 /4 no fibrils were observed.…”
Section: Study Of the Interactions Of Fc-peptides With Ab 12-28mentioning
confidence: 98%
“…These observations are supported by other results, indicating that hydrophobic and ionic interactions play an important role in the aggregation of Ab. [15] These effects may be responsible for the dramatic differences in the propensities of 1-4 to interfere with Ab aggregation.…”
Section: Study Of the Interactions Of Fc-peptides With Ab 12-28mentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, small peptide ligands may serve as an alternative tool for the recognition of Ab aggregates and require no precise protein folding for binding to targets. 30,[37][38][39][40][41] However, potential of resulting peptides as a probe for Ab aggregates and the related binding sites within Ab have not been thoroughly examined. Peptide ligands can also be conjugated to other molecular scaffolds with precise control of spatial orientation, broadening the scope of sensing formats.…”
Section: Introductionmentioning
confidence: 99%